Frother structure–property relationship: Effect of alkyl chain length in alcohols and polyglycol ethers on bubble rise velocity. (September 2016) - Tan, Yue Hua; Finch, James A.
Graphical abstract: Highlights: Bubble rise velocity is decided by alkyl chain length in both alcohols and polyglycols. Longer alkyl chain frothers give lower bubble rise velocity. Carbon number controls hydrophobicity, surface tension gradient and packing and thus rise velocity. Abstract: In mineral flotation, frothers are used to produce fine bubbles, reduce bubble rise velocity, and stabilize the froth, three properties that enhance the flotation process. These properties depend on the frother structure and this paper is part of an investigation into the frother structure-property relationship. The property here is bubble rise velocity and the structural variation is alkyl chain length of two frother families, alcohols and polyglycols. Single bubble rise velocity profiles were determined in a 350 cm column. Velocity at 300 cm as a function of concentration is determined and as a measure of the impact of structure on reduction in bubble rise velocity the concentration at minimum velocity (CMV) is estimated. The effect of increasing alkyl chain length is to decrease CMV by about ca. 90% in alcohols and ca. 70% in polyglycols for every one carbon addition. Taking log CMV as a function of the number of carbons in the alkyl chain gives a series of self-similar linear plots. An argument relating bubble rise velocity to surfactant molecule packing on the bubble surface is proposed.